PERANCANGAN WEB PEMESANAN TIKET PESAWAT BERBASIS REACTJS - Farrel Farhan (Prosiding Seminar Nasional Indonesia, 2026)
An airline ticket booking website is a modern digital solution that provides convenience in air travel ticket purchasing. This study presents the development of a web-based airline ticket booking system using the ReactJS framework to create a responsive, dynamic, and intuitive user interface, combined with the Scrum methodology to support flexible and adaptive project management. ReactJS was selected for its component-based architecture, which supports reusable UI components, strong application performance, and an interactive user experience. The Scrum framework facilitates iterative development through structured sprint cycles, encouraging team collaboration, clear communication, and continuous system refinement in response to changing user requirements. The developed system offers key features such as flight search, seat selection, and a secure and user-friendly payment process. In addition, the integration between front-end and back-end systems through APIs supports data exchange and system maintainability. The results show that the integration of ReactJS and Scrum can produce a reliable and adaptable airline ticket booking system that aligns with current technological developments and user needs in the aviation industry.